Hubungan Dukungan Keluarga terhadap Kualitas Hidup Pasien Penyakit Kronis yang Mendapatkan Perawatan Paliatif - Romadhonia, Hanan Nofiana; Hudiyawati, Dian (Jurnal Gema Keperawatan, 2025)
Family support plays an important role in helping chronic disease patients who receive palliative care. Family support can reduce symptoms and improve the quality of life of patients because it can create a sense of security, comfort, motivation, and help meet physical and emotional needs during treatment. This study aims to determine the relationship between family support and the quality of life of chronic disease patients undergoing palliative care at Dr. Moewardi Hospital. The study design used a descriptive correlative method with a cross-sectional approach. The study sample consisted of 137 respondents selected using a purposive sampling technique. The variables in this study included the independent variable, namely family support, while the dependent variable was quality of life. The instruments used were the Family Support Scale (FSS) questionnaire to measure family support and the WHOQOL-BREF questionnaire to assess quality of life. Data analysis used the Spearman's Rho test. The results showed that the majority of elderly respondents aged 60-90 years old, female, received good family support (58 respondents (42,3%), and the majority had a high quality of life (87 respondents (63,5%). The results of the analysis test showed that there was a positive and very strong relationship between family support and quality of life with a value of p = 0,001 and r = 0,853. The conclusion obtained in this study is that there is a relationship between family support and quality of life in chronic disease patients who receive palliative care.